1109. Valgancyclovir Dosing for Cytomegalovirus Prophylaxis in Heart Transplant Recipients. (31st December 2020) - Huang, Glen; Davis, Matthew R; Beaird, Omer E; Carlson, Margrit; Gaynor, Pryce; Multani, Ashrit; Deng, Mario; Nsair, Ali; Schaenman, Joanna M
Abstract: Background: Cytomegalovirus (CMV) is one of the most common infections after transplantation and continues to cause significant morbidity and mortality. Current guidelines recommend 3-6 months of post-transplant prophylaxis with 900mg daily of valganciclovir in heart transplant recipients. At our institution, however, the protocol is to use 450mg daily of valganciclovir for 6-12 months for intermediate risk (R+) patients and 900 mg daily for high risk (D+/R-) patients. In this study we aimed to identify underlying patient characteristics associated with detectable viral load above the quantifiable threshold. Table 1. Comparison of patients with a CMV viral above and below 137. Methods: We retrospectively reviewed medical records of adult (≥ 18 years) heart transplant recipients with detectable CMV viremia from 2016-2018 resulted during routine clinical screening. Results: Ninety-seven heart transplant recipients with a detectable CMV viral load were identified. Of those, 38 (37.2%) had a quantifiable viral load above the 137 IU/mL threshold. When compared to the individuals with a detectable viral load below the threshold (< 137 IU/mL), they had similar age at time of transplant, increased likelihood of donor/recipient CMV IgG mismatch, and were more frequently on 900mg daily of prophylaxis at time of viremia. Of the individuals with CMV DNAemia above the threshold, the median time to viremia was 271.4 days and the median peak viral load was 701 IU/mL. When limiting analysis to only recipients who were CMV IgG positive, patients with viremia had similar age and more likely to be on 900mg daily of valganciclovir as prophylaxis when compared to individuals with CMV viremia < 137 IU/mL. When comparing CMV D+/R- patients, age and rates of 900mg valganciclovir as prophylaxis were similar (Table 1). Conclusion: We found that despite receipt of CMV prophylaxis, an appreciable number of both R+ and D-/R+ heart transplant recipients developed breakthrough DNAemia despite being on prophylaxis of valganciclovir as recommended by guidelines. Despite receipt of the higher 900 mg daily dose, high risk patients had higher rates of breakthrough DNAemia at our institution compared with R+ intermediate risk patients. More research is needed to evaluate the optimal dose and duration for prophylaxis in heart transplant patients against CMV. Disclosures: All Authors : No reported disclosures